Closing routes to retirement: how do people respond? - Geyer, Johannes; Welteke, Clara (Berlin, 2017)
"We present quasi-experimental evidence on the employment effects of an unprecedented large increase in the early retirement age (ERA). Raising the ERA has the potential to extend contribution periods and to reduce the number of pension beneficiaries at the same time, if employment exits are successfully delayed. However, workers may not be able to work longer or may choose other social support programs as exit routes from employment. We study the effects of the ERA increase on employment and potential program substitution in a regression-discontinuity framework. Germany abolished an important early retirement program for women born after 1951, effectively raising the ERA for women by three years. We analyze the effects of this huge increase on employment, unemployment, disability pensions, and inactivity rates. Our results suggest that the reform increased both employment and unemployment rates of women age 60 and over. However, we do not find evidence for active program substitution from employment into alternative social support programs. Instead employed women remained employed and unemployed women remained unemployed. The results suggest an increase in inequality within the affected cohorts."